Kompetensi Manajemen Kelas Guru di Kelas IV MIS Al Jamiatul Ikhlas Tanjungbalai - Fahreza, Wiwid (Inspiratif Pendidikan, 2024)
This research was conducted to find out how teacher competence is in managing their classes, especially in class IV MIS Al Jamiatul Ikhlas Tanjungbalai. Using a qualitative research approach and a descriptive study with research subjects being classrooms, teaching and learning activities, and the homeroom teacher of class IV MIS Al Jamiatul Ikhlas Tanjungbalai. The research instruments used were observation instruments, interview guides, and documentation. The results obtained show that the class management competence of teachers in class IV MIS Al Jamiatul Ikhlas is still relatively low because they are only able to maximize one of the four managerial aspects of the class, namely the socio-emotional aspect, while the aspects that have not been fulfilled are the physical, organizational and technical administrative aspects. Teachers also have not been able to face the managerial constraints they face.